Cosmological N-body simulations including radiation perturbations - Brandbyge, Jacob; Rampf, Cornelius (Monthly notices of the Royal Astronomical Society. Letters, 2017)
Abstract: Cosmological N-body simulations are the standard tools to study the emergence of the observed large-scale structure of the Universe. Such simulations